2017
DOI: 10.1016/j.carres.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolytic cleavage of naphthylmethyl ethers in the presence of sulfides

Abstract: With the aid of a series of model thioether or thioglycoside containing polyols protected with combinations of benzyl ethers and 2-naphthylmethyl ethers it is demonstrated that the latter are readily cleaved selectively under hydrogenolytic conditions in the presence of the frequently catalyst-poisoning sulfides. These results suggest the possibility of employing 2-naphthylmethyl ethers in place of benzyl ethers in synthetic schemes when hydrogenolytic deprotection is anticipated in the presence of thioether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…An alternative intramolecular aglycone delivery (IAD) approach pioneered by Ogawa and Ito [27][28][29] was also investigated. After initially investigating a mannosyl substrate which included a p-methoxybenzyl group at O-2, the best results were obtained using 2-O-Nap protected thiomannoside 9 30 that gave acetal 10 on treatment with DDQ and reaction with 7 (Scheme 3, Method 4). Activation of the thiophenyl group with diphenyl sulfoxide and Tf 2 O gave mannoside 11 in 45% yield over the two steps with high β-selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative intramolecular aglycone delivery (IAD) approach pioneered by Ogawa and Ito [27][28][29] was also investigated. After initially investigating a mannosyl substrate which included a p-methoxybenzyl group at O-2, the best results were obtained using 2-O-Nap protected thiomannoside 9 30 that gave acetal 10 on treatment with DDQ and reaction with 7 (Scheme 3, Method 4). Activation of the thiophenyl group with diphenyl sulfoxide and Tf 2 O gave mannoside 11 in 45% yield over the two steps with high β-selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The removal of benzyl groups using hydrogenolysis is difficult, as the sulfur atom can poison the catalyst but the chemoselective removal of 2-naphthylmethyl ether protecting groups in the presence of benzyl ethers on thioglycosides has been demonstrated. 332 A new oxidative photocatalytic method for benzyl ether removal can overcome this challenge. 333 Oxidation reactions, e.g.…”
Section: Commonly Used Glycosylating Agentsmentioning
confidence: 99%
“…To overcome this problem, a variety of new reagent combinations were introduced which increase the utility of Nap Protecting group. For example, Bennett employed β‐pinene as acid scavenger, Crich used hydrogenation using Pd/C poisoned with thioether, Codée discovered HCl and HFIP, and Liu introduced HF‐pyridine as novel reagents. Borbas and co‐workers recently showed that catalytic hydrogenation can be effectively used for selective deprotection of the (2‐naphthyl)methyl (NAP) group in the presence of p ‐methoxybenzyl (PMB), benzyl and benzylidene groups in a series of monosaccharides .…”
Section: New Reagents For Old Protecting Groupsmentioning
confidence: 99%